2021
DOI: 10.1249/mss.0000000000002657
|View full text |Cite
|
Sign up to set email alerts
|

Age of First Exposure to Collision Sports Does Not Affect Patient Reported Outcomes in Women and Men Community Rugby Players

Abstract: Purpose: This study aimed to determine the relationship between age of first exposure (AFE) to repetitive head impacts through contact/collision sports and patient-reported outcomes in community rugby players. Methods: We recruited community rugby players older than 18 yr with at least 1 yr of contact rugby participation to complete an online survey. Participants completed the Brief Symptom Inventory-18 (BSI-18), Short-Form Health Survey 12 (SF-12), and Satisfaction with Life Scale (SWLS) via Qualtrics. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
(142 reference statements)
0
7
0
Order By: Relevance
“…Hunzinger et al ( 121 ) surveyed 1,034 current and former community-level rugby players. Participants completed patient-reported outcomes, including the Brief Symptom Inventory 18 to assess psychological distress, the Short Form Health Survey 12 to assess physical and mental health quality of life, and the Satisfaction with Life Scale.…”
Section: Studies With Retired Amateur and Professional Athletesmentioning
confidence: 99%
“…Hunzinger et al ( 121 ) surveyed 1,034 current and former community-level rugby players. Participants completed patient-reported outcomes, including the Brief Symptom Inventory 18 to assess psychological distress, the Short Form Health Survey 12 to assess physical and mental health quality of life, and the Satisfaction with Life Scale.…”
Section: Studies With Retired Amateur and Professional Athletesmentioning
confidence: 99%
“… 19 Similarly, recent investigations of middle-aged former American football players and American amateur rugby players (male and female) reported that career duration was unrelated to later-life or mid-life health conditions and dysfunction. 11 , 39 , 41 Taken together, data among physically active early- to mid-adult collision sport athletes (i.e., aged 22–50 years) suggest that RHI exposure does not adversely affect objective measures of neurobehavioral health; 3 however, the later-life effects (i.e., older adults aged >65 years) and the effects in physically inactive individuals with histories of prolonged RHI exposure (e.g., former adult rugby players who are inactive) remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, this method was chosen based on the recommendation of the NINDS traumatic encephalopathy syndrome consensus statement and has been previously utilized in other research as a measure of RHI exposure because it permits a rough estimation in the absence of biomechanical data, which is not feasible to collect across the lifespan. 3 , 7 , 11 Lastly, this study relied on self-reported measures of physical activity as a dichotomous outcome (yes/no for meeting American College of Sports Medicine physical activity guidelines). Although self-reported measures of physical activity have been used in previous research, 54 they may fail to capture the accuracy and precision needed to detect the true effects of exercise (i.e., frequency, intensity, type, time) on the included outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations